Может ли робот творить? - Колесниченко, Н. Ю. (ХНУРЕ, 2020)
The author of this work is trying to answer the question of whether the process of creating a cultural product that made by robot can be called a creative act. Also revealed the concept of “creativity” and its significance for a person is considered. Author made comparison between the creative work of man and robot.In particular, answer was given to the question of, whether it is worth considering the robot as an independent "creator", or is it just a tool for solving human problems.
Keywords: философия; робот